Precursor impact and mechanism analysis of uranium elimination by biochar supported sulfurized nanoscale zero-valent iron. Issue 2 (April 2022) - Pang, Hongwei; Zhang, Enyao; Zhang, Di; Wang, Xiangxue; Zhao, Bing; Liu, Lijie; Ma, Xiaoying; Song, Gang; Yu, Shujun
Abstract: The potential threat of radionuclide uranium from nuclear industry had attracted worldwide attention because both environment and human beings were menaced. Nowadays, modified nanoscale zero valent iron (NZVI) had been reported to be efficient in U(VI) elimination due to its high reactivity, reducibility, and availability. In this study, serial biochar-based sulfide NZVIs (BC-SNZVIs) with different C/Fe and S/Fe were synthesized and applied to the elimination of U(VI) in order to investigate the effect of iron, sulfur, and biochar precursor. The morphological investigations indicated the precursor played an essential role towards BC-SNZVIs on their dispersibility and structure. The XRD analyzes were conducted to study their crystalline structure and the BC1.0 -S0.14 NZVI showed outstanding stability after 10-day exposure under atmosphere. The excellent magnetism was confirmed via VSM study, and BC1.0 -S0.14 NZVI could be easily and rapidly separated from aqueous solution. The batch kinetic and isothermal studies illustrated the superior performances towards U(VI), and the results revealed the fast kinetics and high capacities of BC-SNZVIs. Finally, the removal mechanism was explored by using XPS technology and pH-effect experiment. U(VI) was adsorbed by BC matrix and SNZVI, while portion of U(VI) was reduced into U(IV) by Fe 0 inner core. The elimination process of U(VI) towards BC-SNZVI was confirmed to be a synergistic effect of adsorption and reduction. This study verified the optimal ratio of C/Fe and S/Fe, and explained the removal mechanism in detail, which was beneficial to further investigations of NZVI-based and biochar-based materials. Graphical Abstract: ga1 Highlights: The impact of C/Fe and S/Fe ratios on biochar-based SNZVIs were investigated. BC1.0 -S0.14 NZVI showed excellent attraction and outstanding performance to U(VI). The removal mechanism was a synergistic effect of reduction and adsorption.